Show that the cubic function f(x) = x^3 - 7x - 6 has a root x = -1 and hence factorise it fully.

f(-1) = (-1)^3 - (-1)*7 - 6 = -1 + 7 - 6 = 0

Hence f(x) = (x+1)(x^2 + ax - 6)

Expand this out

f(x) = x^3 + ax^2 - 6x + x^2 + ax - 6 

      = x^3 + (a+1)x^2 + (a-6)x -6

By comparing co-efficients

a + 1 = 0

a - 6 = -7

a = -1

Thus 

f(x) = (x + 1)(x^2 - x - 6)

      = (x + 1)(x - 3)(x + 2)

Answered by James B. Maths tutor

3855 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

The curve C has equation y=(2x-3)^5, the point P lies on C and has coordinates (w, – 32), find (a) the value of w and (b) the equation of the tangent to C at the point P in the form y=mx+c , where m and c are constants.


(i) Prove sin(θ)/cos(θ) + cos(θ)/sin(θ) = 2cosec(2θ) , (ii) draw draph of y = 2cosec(2θ) for 0<θ< 360°, (iii) solve to 1 d.p. : sin(θ)/cos(θ) + cos(θ)/sin(θ) = 3.


The Curve C has equation y = 3x^4 - 8x^3 - 3. Find dy/dx.


How can I differentiate x^2+2y=y^2+4 with respect to x?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences